Women's perspectives on motivational factors for lifestyle changes after gestational diabetes and implications for diabetes prevention interventions. Issue 3 (19th March 2021) - Ørtenblad, Lisbeth; Høtoft, Diana; Krogh, Rubab H.; Lynggaard, Vibeke; Juel Christiansen, Jens; Vinther Nielsen, Claus; Hedeager Momsen, Anne‐Mette
Abstract: Introduction: Gestational diabetes mellitus (GDM) is a common complication in pregnancy and constitutes a public health problem due to the risk of developing diabetes and other diseases. Most women face barriers in complying with preventive programs. This study aimed to explore motivational factors for lifestyle changes among women with a history of GDM and their suggestions for preventive programs. Methods: This study used a qualitative approach in six focus group interviews with a total of 32 women. The selection criteria were time since onset of GDM, including women diagnosed with GDM, six months and five years after GDM, diagnosed and not diagnosed with diabetes. Inductive analysis was performed. Results: The women reacted with anxiety about their GDM diagnosis and experienced persistent concerns about the consequences of GDM. They were highly motivated to take preventive initiatives, but faced major adherence challenges. The demotivating factors were lack of time and resources, too little family involvement, lack of knowledge and social norms that may obstruct healthy eating. A powerful motivational factor for complying with preventive strategies was the well‐being of their children and partners. Conclusions: Preventive initiatives should be rooted in the women's perception of GDM/diabetes and based on their experiences with barriers and motivational factors. The well‐being and the quality of life within the family are dominant motivational factors which offer powerful potentials for supporting the women's coping capability. Further, there is a need to be responsiveness to the women and their families even a long time after the onset of GDM. Abstract : Even a long time after GDM the women are worried about the health consequences of the diagnosis and all though motivated to take preventive actions they experience barriers to adhere to the recommended lifestyle changes. To better overcome such barriers the women's recommend preventive initiatives to be rooted at the core of their everyday life and to include their families. It is important to pay attention to the women for a long time after the GDM diagnosis and to base preventive programs within the women's perspectives of GDM/diabetes and preventive initiatives.